2011
DOI: 10.1099/jmm.0.026807-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of human rotavirus genotype G9 in metropolitan Detroit between 2007 and 2009

Abstract: , rotavirus (RV)-positive stool samples from 238 children with acute gastroenteritis, seen at Children's Hospital of Michigan in Detroit, USA, were collected and RV genotyping was performed. G and P genotypes were determined by RT-PCR and nucleotide sequencing was conducted on selected G9 and P[6] strains. Correlation between the severity of gastroenteritis episode and the infecting G genotype was done using a 14-point scoring system. The predominant G genotype was G9 (39.5 %), followed by G1 (35.3 %) and G4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
5
0
2
Order By: Relevance
“…13,[16][17][18][19] Variable prevalence rates of G9 RVA strains have been also reported between 27% and 62% among geographical areas like Cuba, France, Mexico, and USA where G9 RVs strains have emerged. [20][21][22] Circulation of these G9 RVA strains in different lineages and sublineages has also been reported earlier. 23 These RVA G9P [8] strains have been under circulation and found to cause symptomatic infections among children <5 years of age, who were expected to be protected by the pre-existing immunity which would provide heterotypic protection against common genotypes.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…13,[16][17][18][19] Variable prevalence rates of G9 RVA strains have been also reported between 27% and 62% among geographical areas like Cuba, France, Mexico, and USA where G9 RVs strains have emerged. [20][21][22] Circulation of these G9 RVA strains in different lineages and sublineages has also been reported earlier. 23 These RVA G9P [8] strains have been under circulation and found to cause symptomatic infections among children <5 years of age, who were expected to be protected by the pre-existing immunity which would provide heterotypic protection against common genotypes.…”
Section: Introductionsupporting
confidence: 64%
“…Ever since 1995, rapid spread of G9 RVA has been reported worldwide making them now the major human RVA genotype . Variable prevalence rates of G9 RVA strains have been also reported between 27% and 62% among geographical areas like Cuba, France, Mexico, and USA where G9 RVs strains have emerged . Circulation of these G9 RVA strains in different lineages and sublineages has also been reported earlier .…”
Section: Introductionmentioning
confidence: 69%
“…It remains unclear whether widespread implementation of RV vaccines causes the emergence of non-vaccine genotypes. Recent regional epidemiological studies have confirmed the high prevalence of the genotype G9, reaching 50%-90% in some circumstances (25). RV genotype diversity, especially that of G9 and G12, is a great challenge for current vaccination programs (11).…”
Section: Discussionmentioning
confidence: 99%
“…The first G9 strain, WI91, was detected in children in the United States in 1983 [22] and was first detected in 2002 in South Korea [14] . G9 has become recognized as one of the emerging genotypes in many countries such as Cuba [23] , France [24] , Mexico [25] , the United States [26] , and Libya [27] . In this study, G9s were the third most identified genotype and had a slightly greater predominance over G3 and G4.…”
Section: Discussionmentioning
confidence: 99%